Pembuatan Dashboard Sederhana Sebagai Media Representasi Data Penjualan UMKM - Hariani, Ermatry; Febriyastuti Widyawati, Retno; Fikri Firmansyah, Mochammad; Ari Saputra, Diantok; Nur Diana, Livi (PELITA NUSA TENGGARA, 2023)
Along with the development of the world of information technology that is increasingly advanced, more and more companies are trying to improve their business which is closely related to information technology itself. One example of technological development is the existence of computers. The use of computers in this business activity is to provide information quickly and precisely. Companies that want to achieve success must follow the information age by using data processing support tools, namely computers. Data processing on computers is very helpful for Micro, Small & Medium Enterprises (MSMEs) in providing data information from the results of their sales. The data information can be presented in the form of a simple dashboard. Dashboard is a visual display of important information that organizes information in one layer so that it can be monitored. The purpose of this community service is to provide education to MSME actors regarding the creation of a simple dashboard. The method used is with Focus Group Discussion (FGD) via online / online. The result of this service is to provide convenience for MSME actors in presenting information from their sales data. The implications of this activity are to improve the skills and knowledge of MSME actors in their business activities.